Beyond the law?: laypeople in law, civil disobedience, and conceptions of violence - Legnaro, Aldo (Laypeople in law, 2024)
Acts of civil disobedience and the definition of violence are closely linked because in individual cases, it is not necessarily clear which actions should be considered violent or non-violent. While the actors who participate in civil disobedience - who are mostly laypeople in law - generally consider their actions to be non-violent and legitimate in light of an overarching goal, the legal system often defines these actions as violent and illegal - a distinction that depends largely on the interpretation of the applicable law. Fifty years of German protest history provide various examples. Drawing on the sit-in blockades of the 1980s against rearmament and the 2022 superglue protests against climate policy, the chapter traces the judicial processing of civil disobedience with regard to the question of whether the actions of laypeople in law exert an influence on legal interpretations of violence. Narrow definitions of the legal system are demonstrated to have softened in a decades-long development without having been rendered entirely ineffective. This finding demonstrates the social productivity that practices of civil disobedience can have when coupled with civic courage. Laypeople in law can influence judicial interpretations of violence when they combine extra-legal forms of disobedient action with intra-legal perseverance in terms of going through the courts, although this success may rest on shaky ground.